Antitrust Standing: Congress Responds to Illinois Brick - Morris B. Hoffman (Washington University Law Quarterly, 1978)
This Article will assess the impact of S. 1874 in light of the history and development of standing notions in antitrust law.
Keywords: Antitrust law – Damages; Standing to sue